Environment and host identity structure communities of green algal symbionts in lichens. Issue 1 (11th September 2017) - Dal Grande, Francesco; Rolshausen, Gregor; Divakar, Pradeep K.; Crespo, Ana; Otte, Jürgen; Schleuning, Matthias; Schmitt, Imke
Summary: An understanding of how biotic interactions shape species' distributions is central to predicting host–symbiont responses under climate change. Switches to locally adapted algae have been proposed to be an adaptive strategy of lichen‐forming fungi to cope with environmental change. However, it is unclear how lichen photobionts respond to environmental gradients, and whether they play a role in determining the fungal host's upper and lower elevational limits. Deep‐coverage Illumina DNA metabarcoding was used to track changes in the community composition of Trebouxia algae associated with two phylogenetically closely related, but ecologically divergent fungal hosts along a steep altitudinal gradient in the Mediterranean region. We detected the presence of multiple Trebouxia species in the majority of thalli. Both altitude and host genetic identity were strong predictors of photobiont community assembly in these two species. The predominantly clonally dispersing fungus showed stronger altitudinal structuring of photobiont communities than the sexually reproducing host. Elevation ranges of the host were not limited by the lack of compatible photobionts. Our study sheds light on the processes guiding the formation and distribution of specific fungal–algal combinations in the lichen symbiosis. The effect of environmental filtering acting on both symbiotic partners appears to shape the distribution of lichens.